2012
DOI: 10.1111/jocn.12032
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of dementia patient's quality of life and influencing factors in two cities

Abstract: Nurses could implement interventions to focus on many of the patient's influencing factors, so that to improve their mental and physical health, which may slow the disease process and further improve the patient's quality of life. In addition, Chinese government could learn some experience from Japanese government, such as perfect the system of nursing insurance for elderly and introduce professional geriatric nursing talents to provide better service for the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
(43 reference statements)
0
11
0
1
Order By: Relevance
“…Conducting reminiscence therapy for older people in a variety of environments (e.g., facilities, home nursing) will be very efficient. Li et al (2012) reported that effective nursing intervention is important to slow the progression of dementia and improve quality of life. Reminiscence therapy is one such effective intervention.…”
Section: Discussionmentioning
confidence: 98%
“…Conducting reminiscence therapy for older people in a variety of environments (e.g., facilities, home nursing) will be very efficient. Li et al (2012) reported that effective nursing intervention is important to slow the progression of dementia and improve quality of life. Reminiscence therapy is one such effective intervention.…”
Section: Discussionmentioning
confidence: 98%
“…Although there are nine studies did not find any relationship between demographic characteristics and QoL (Andersen et al, 2004;Grske et al, 2014;Moyle et al, 2015;Monteiro et al, 2014;Sloane et al, 2005;Winzelberg et al, 2005;Wetzels et al, 2010;Salvador et al, 2000), other studies found that higher education (Marventano et al, 2015;Li et al, 2012), males (Woods et al, 2014;Barca et al 2011), white (Black et al, 2012), widowed (Samus et al, 2005) and extroverted characteristic (Li et al, 2012) tended to be positively associated with better QoL for elderly people with dementia. Moreover, Banerjee et al (2005) found that QoL of people with dementia showed decline as with the increasing age, while Mjørud et al (2014) indicated that the QoL was worse among the youngest (<79) and oldest (>90) people with dementia.…”
Section: Demographic Characteristicsmentioning
confidence: 98%
“…Four studies (Fukushima et al, 2004;Nikmat et al, 2015;Li et al, 2012;Byrne et al, 2006) explored the association between financial status and QoL for 26 elderly people with dementia, and the results suggested that financial security is a key factor in determining QoL. Additionally, quality of dementia care is also an essential factor influencing QoL.…”
Section: Religious Environmental and Other Factorsmentioning
confidence: 99%
See 2 more Smart Citations